DEPENDENCE OF PLAYING ONLINE GAMES WITH TIME MANAGEMENT AND PRO-SOCIAL BEHAVIOR - Yoessy Etna Werdini; Suroso Suroso; Tatik Meiyutariningsih (Airlangga Journal of Innovation Management, 2021)
The purpose of this research is to know the relationship of dependence of playing online games with time management and behavioural prososial. Time management is an ability of students in use of time,that can set goals, priorities, and do control time in self-regulation. Prososial behavior is an action that encourages someone to do interpersonal relationships, working, honest and helping others. Online game addiction is a state of person who are tied to very strong habits and cannot off to play games online from time to time regardless of a negative impact to them. Analysis method used is quantitative approach using Product Moment Correlation technique of using 96 samples in class 2 State Junior High School 13 on Surabaya city. The result showed a positive relationship of dependence play online games with time management retrieved value rxy = 0.291 with probability of 0.004 (p < 0.05) there is a positive relationship of dependence with online gaming behavior prososial retrieved values rxy2 = 0.339 with probabili ties of 0.001 (p < 0.05). Thoose, the hypothesis about negative relationships between dependency play online games with time management and prosocial behavior, denied.